Implementation of Ijarah in Efforts to Improve Farmer Welfare - Ninit Firdayanti; Renny Oktafia (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
Agricultural land has a large area and is useful for farmers, but not all villagers work as farmers due to limited funds and need money, so they prefer to rent it. This study aimed to determine the application of the ijarah contract and its impact on the agricultural sector. This study uses a qualitative method by applying a case study approach to obtain information directly from informants based on current cases. This study indicates that the application of agricultural land leases in Garung Village is following Islamic law. Several informants differ in explanations regarding the nominal fee of ujrah, year, and the expiration of agricultural land lease agreements. At the same time, the impact on landowners cannot improve welfare from religious indicators and souls. Still, it can improve welfare from indicators of religion, life, mind, descent, and property in terms of land tenants.